Kondisi masyarakat Arab pra Islam dan penerapan metode Team Games Tourmament (TGT) dalam pembelajaran - Mukharomah, Awwalina (Maliki Interdisciplinary Journal, 2023)
This paper aims to explore the social, economic, and political conditions of pre-Islamic Arab society. The pre-Islamic period is often referred to as the Age of Jahiliyah or stupidity, even though if explored further, pre-Islamic Arab society already had an advanced civilization, it's just that they didn't have the right knowledge regarding morals and religion. The condition of pre-Islamic Arab society needs to be fully understood by students, so a learning method is needed that can facilitate them to gain this understanding. The method used is library research, which is conducted by examining written sources about the social, economic, and political conditions of pre-Islamic Arab society as well as appropriate learning methods to be given in class. The results found were that pre-Islamic Arab society had poor moral and social conditions, they loved poetry, worshiped statues, and had advanced economic conditions in trade and agriculture. Pre-Islamic Arab society implemented a tribal political system led by leaders who were elected based on honor and wealth. The appropriate learning method to be applied to the material conditions of pre-Islamic Arab society is the Team Games Tournament (TGT) method which can stimulate critical thinking, foster motivation and social awareness of students.